Entomopathogen Bacteria as Biocontrol Agents against Insect Pests - Zulyusri; Dini Rohadatul Aisya; Tomi Apra Sentosa (Jurnal Online Pertanian Tropik, 2023)
Insects are animals that have the potential to become pests. One way to control insect pests that are environmentally friendly is by using entomopathogenic bacteria. Bacteria are one of the biocontrol agents that are found in various places and have mass production that is faster than other microorganisms. This study aims to explain the types of entomopathogenic bacteria that act as insect pest controllers for agriculture. The type of research used in this study is Systematic Literature Review. The data used was obtained from the analysis of 80 articles related to issue 2014-2022 . Article which is used is collected by searching the database Google Scholar and ERIC. The results showed that there were several types of pathogenic bacteria against insects, including Bacillus thuringiensis against cockroaches, Serratia entomophila against stem planthoppers, Serratia proteamaculans against the Coconut Beetle, and Serratia wilting against the Coconut Beetle.